Rachel Vennya Persuasive Communication Strategy to Improve Her Personal Branding on Instagram - Anisqha Maia Putri; Yohan Chandra Agustine; Wahyunengsih Wahyunengsih (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2022)
The purpose of this study is to identify the types of persuasive communication strategies used by Rachel Vennya in the content uploaded on her personal Instagram account. Second, to know the characteristics of Personal branding. This research uses a qualitative approach that aims to explore something in depth. This qualitative research contains a literature review, theoretical concepts related to the research problem, namely the problem of using persuasive strategies and personal branding in building personal branding. The results show that Rachel Vennya uses persuasive communication strategies, namely psychodynamic strategies, sociocultural strategies and the meaning constructions. Rachel Vennya has also applied the characteristics of a personal branding, namely uniqueness, relevance, and consistency.